Reconocemos nuestras emociones - Sánchez Basilio, Maribel Analí (2019)
The present work of professional sufficiency aims to promote the promote the meaningful learning according to the competence: builds your identity and ability: regulate your emotions in the first grade of primary education. _x000D_ The learning session corresponds to the area of social personnel wich hass been prepared and executed following the recommendations of the personal development approach that empharizes the development process that leads human beings to building themselves as people, reaching their maximum potential in a constant process of biological cognitive, affective behavioral and social transformations that happen throughout life. which has been proposed by the Ministry of Education, as well as the pedagogical and didactic processes necessary which are necessary for the achievement of competency learning. _x000D_ The learning session will be evaluated by a checklist that will verify the level of learning achieved by the student.